Protocol to generate a 3D atherogenesis-on-chip model for studying endothelial-macrophage crosstalk in atherogenesis - Katie M.L. Hanford; Kim E. Dzobo; Miranda Versloot; Jorge Peter; Jeffrey Kroon (STAR Protocols)
Summary: The endothelium is the gatekeeper of vessel health, and its dysfunction is pivotal in driving atherogenesis. Here, we present a protocol to replicate endothelial-macrophage crosstalk during atherogenesis, called the “atherogenesis-on-chip” model, based on the Emulate dual-channel perfusion system. We describe a model for studying endothelial-macrophage interactions during atherogenesis in human aortic endothelial cells and human macrophages using qPCR and secretome analysis, fluorescence microscopy, and flow cytometry. This protocol could be adapted toward more complex plaque microenvironment or other disease settings. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.